Software failure prediction based on patterns of multiple-event failures - Santos, Caio Augusto Rodrigues dos (2021)
A fundamental need for software reliability engineering is to comprehend how software systems fail, which means understanding the dynamics that govern different types of failure manifestation. In this research, I present an exploratory study on multiple-event failures, which is a failure manifestation characterized by sequences of failure events, varying in terms of length, duration, and combination of failure types. This study aims to (i) improve the understanding of multiple-event failures in real software systems, investigating their occurrences, associations, and causes; (ii) propose analysis protocols that take into account multiple-event failure manifestations; (iii) take advantage of the sequential nature of this type of software failure to perform predictions. The failures analyzed in this research were observed empirically. In total, I analyzed 42,209 real software failures from 644 computers used in different workplaces. The major contributions of this study are a protocol developed to investigate the existence of patterns of failure associations; a protocol to discover patterns of failure sequences; and a prediction approach whose main concept is to calculate the probability of a certain failure event to occur within a time interval upon the occurrence of a particular pattern of preceding failures. I used three methods to tackle the prediction problem; Multinomial Logistic Regression (w/ and w/o Ridge regularization), Decision Tree, and Random Forest. These methods were chosen due to the nature of the failure data, in which the failure types must be handled as categorical variables. Initially, I performed a failure association discovery analysis which only included failures from a widely used commercial off-the-shelf Operating System (OS). As a result, I discovered 45 OS failure association patterns with 153,511 occurrences, which were composed of the same or different failure types and occurring within well-established time intervals, systematically. The observed associations suggest the existence of underlying mechanisms governing these failure occurrences, which motivated the improvement of the previous method by creating a protocol to discover patterns of failure sequences using flexible time thresholds and a failure prediction approach. To have a comprehensive view of how different software failures may affect each other, both methods were applied to three different samples — the first sample contained only OS failures, the second contained only User Application failures, and the third encompassed both OS and User Application failures altogether. As a result, I found 165, 480, and 640 different failure sequences with thousands of occurrences, respectively. Finally, the proposed approach was able to predict failures with good to high accuracy (86% to 93%).